EMPREGO DA ANASTOMOSE DE ROUX EM "Y" NO TRATAMENTO ALTERNATIVO DAS SÃNDROMES PÓS-GASTRECTOMIAS (Veterinária Notícias, 2014)
EMPREGO DA ANASTOMOSE DE ROUX EM "Y" NO TRATAMENTO ALTERNATIVO DAS SÃNDROMES PÓS-GASTRECTOMIAS